Attributes of business incubators: A conjoint analysis of venture capitalist's decision making - Michele Manconi; Salvatore Bellomo; Anna Nosella; Lara Agostini (Journal of Risk and Financial Management, 2022)
Startups contribute significantly to the economic development of a country. Despite their importance and promising future, they are extremely fragile, mainly for their lack of tangible and intangible resources. Since this can be obtained through an incubation process, business incubators (BIs) could have a significant impact on the survival rate of startups. Once defined their core structure and value proposition, there are other players, such as venture capitalists who could guarantee the funds necessary to make the startup's business grow over time. Drawing on the resource-based view theory, this research explores whether some BIs could represent a certification of startup quality for venture capitalists (VCs). Specifically, we investigate whether some specific attributes of BIs increase the probability that a VC funds startups after being incubated; to this purpose, we carry out an experiment on a European sample of VCs. Results demonstrate that some characteristics of the BI can produce a sort of certification effect to the incubated startups, increasing the probability of being funded by VCs.
Keywords: 650; business incubator; conjoint analysis; venture capital